Investigation on Magnetic Properties of Hematite Superstructures with Controlled Microstructures - Haisheng Qian; Guchang Han; Hong Yang; Guofeng Lin; Rong Xu (ASEAN Journal of Chemical Engineering, 2008)
Magnetic properties of a series of hematite particles of pseudocubic or pseudoellipsoidal shape consisting of sub-nanoparticles, as well as irregularly shaped hematite agglomerates, were investigated. The microstructures of hematite particles directly obtained from a hydrothermal process were finely controlled with different experimental conditions, such as the type of counter anion, Fe3+/OH- ratio, surfactant, and aging time. Although samples with different microstructures have a nearly same value of the saturation magnetization, a large variation in the coercivity (Hc) is observed. Hc is found to be closely related to the microcrystal size and its packing density, as well as the formed particle morphologies. The findings obtained in this work contribute to further understanding about the correlation between the microstructural features and the magnetic properties of hematite superstructures. With such fundamental knowledge, it is possible for a systematic search of controlling synthesis parameters which will further lead to the fabrication of hematite particles with optimized magnetic properties for different technological demands.